Carbapenemase-Producing Klebsiella pneumoniae From Transplanted Patients in Brazil: Phylogeny, Resistome, Virulome and Mobile Genetic Elements Harboring blaKPC–2 or blaNDM–1 - Raro, Otávio Hallal Ferreira; da Silva, Ravena Maya Cardoso; Filho, Edison Moraes Rodrigues; Sukiennik, Teresa Cristina Teixeira; Stadnik, Claudio; Dias, Cícero Armídio Gomes; Oteo Iglesias, Jesús; Pérez-Vázquez, María (Frontiers in Microbiology, 2020)
Objectives: Carbapenemase-producing Klebsiella pneumoniae (CP-Kp) is a major cause of infections in transplanted patients and has been associated with high mortality rates in this group. There is a lack of information about the Brazilian structure population of CP-Kp isolated from transplanted patients. By whole-genome sequencing (WGS), we analyzed phylogeny, resistome, virulome of CP-Kp isolates and the structure of plasmids encoding bla KPC-2 and bla NDM-1 genes. Methods: One K. pneumoniae isolated from each selected transplanted patient colonized or infected by CP-Kp over a 16-month period in a hospital complex in Porto Alegre (Brazil) was submitted for WGS. The total number of strains sequenced was 80. The hospital complex in Porto Alegre comprised seven different hospitals. Highresolution SNP typing, core genome multilocus sequence typing (MLST), resistance and virulence genes inference, and plasmid reconstruction were performed in 80 CP-Kp. Results: The mortality rate of CP-Kp colonized or infected transplanted inpatients was 21.3% (17/80). Four CP-Kp epidemic clones were described: ST11/KPC-2, ST16/KPC-2 and ST15/NDM-1, all responsible for inter-hospital outbreaks; and ST437/KPC-2 affecting a single hospital. The average number of acquired resistance and virulence genes was 9 (range 2-14) and 27 (range 6-36), respectively. Two plasmids carrying the bla KPC-2 were constructed and belonged to IncN and IncM types. Additionally, an IncFIB plasmid carrying the bla NDM-1 was described. Conclusions: We detected intra-and inter-hospital spread of mobile structures and international K. pneumoniae clones as ST11, ST16 and ST15 among transplanted patients, which carry a significant range of acquired resistance and virulence genes and keep spreading across the world.